Psychoanalytic Perspectives on Psychosocial Dimensions of Adversity among Black Youth. (3rd April 2022) - Adams, C. Jama
ABSTRACT: This article offers an exploration of the psychological impact of race-driven adversities on Black youth. Sociological data and psychoanalytic perspectives are outlined to contextualize the often less-than-good-enough outcomes for Black youth across all developmental domains. Emphasis is placed on understanding the intrapsychic processes observed in response to race-driven adversities and the therapeutic challenges to addressing the conflicts and compromises.